Correctional populations in the United States, 2013 - Glaze, Lauren E. (Correctional Populations in the United States, 2014)
Presents statistics on offenders supervised by adult correctional systems in the United States at yearend 2013, including offenders supervised in the community on probation or parole and those incarcerated in prison or local jail. The report provides the size and change in the total correctional population during 2013. It details the slowing rate of decline in the population since 2010 and the downward trend in the correctional supervision rate since 2007. It also examines the impact of changes in the community supervision and incarcerated populations on the total correctional population in recent years. Findings cover the size of the male and female correctional populations and compare the rates of change in the populations by correctional status since 2000. Appendix tables provide information on other correctional populations, including prisoners under military jurisdiction, inmates held by correctional authorities in the U.S. territories and commonwealths, and jail inmates held in Indian country facilities, and estimates of the total correctional population by jurisdiction and correctional status. Findings are based on data from several BJS correctional data collections.